2017
DOI: 10.4103/ijmr.ijmr_31_16
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of beta-lactamases, bla NDM-1 phylogeny & plasmid replicons in multidrug-resistant Klebsiella spp. from a tertiary care centre in south India

Abstract: Background & objectives:β-lactamases play a predominant role in drug-resistance amongst Enterobacteriaceae. Presence of genes on transferable plasmids encoding these enzymes favours their dissemination across species and genera within and outside geographical boundaries. This study was aimed to understand the presence of β-lactamases and transferable plasmids in clinical isolates of Klebsiella spp. which can contribute to the spread of resistance determinants.Methods:A total of 41 clinical isolates of Klebsiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Most of the isolates carried bla NDM with one or more ESBL genes. This is in agreement with various studies that have reported co-resistance among clinical isolates [ 36 , 37 ]. These multiple resistance genes found in some isolates, as observed in this study, are indicative of the existence of multidrug resistant pathogens, which are responsible for treatment failure, outbreaks of infections and higher treatment costs [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Most of the isolates carried bla NDM with one or more ESBL genes. This is in agreement with various studies that have reported co-resistance among clinical isolates [ 36 , 37 ]. These multiple resistance genes found in some isolates, as observed in this study, are indicative of the existence of multidrug resistant pathogens, which are responsible for treatment failure, outbreaks of infections and higher treatment costs [ 38 ].…”
Section: Discussionsupporting
confidence: 93%